What is water? : the history of a modern abstraction - Linton, Jamie (Nature, history, society., 2010)
"We all know what water is, and we often take it for granted. But the spectre of a worldwide water crisis suggests there might be something fundamentally wrong with the way we think about water. Jamie Linton dives into the history of water as an abstract concept, stripped of its environmental, social, and cultural contexts. Reduced to a scientific abstraction--to mere H[subscript 2]O--this concept has given modern society licence to dam, divert, and manipulate water with apparent impunity. Part of the solution to the water crisis involves reinvesting water with social content, thus altering the way we see water. What Is Water? offers a fresh approach to a fundamental problem."--Jacket.